2022
DOI: 10.23969/jrak.v14i1.5172
|View full text |Cite
|
Sign up to set email alerts
|

Financial Leverage and Idiosyncratic Risk in Indonesia: Does Integrated Reporting Matter?

Abstract: This study empirically examines the association between financial leverage and idiosyncratic risk. This study also includes integrated reporting elements as moderating variables. This study employs a quantitative approach with secondary data obtained from the www.idx.co.id, www. finance.yahoo.com, and related company websites. The research population includes companies engaged in the manufacturing sector, listed on the IDX in 2016–2020, with a sample of 450 companies based on purposive sampling. The data analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Harjito & Hapsari (2016) and Rajverma et al (2019) concluded that leverage, firm size, and profit before tax are proven to have a negative effect on firm risk. Leverage is a ratio that measures long-term and shortterm debt capacity to finance company assets (Geno et al, 2022). The proxy of leverage in this study is based on Firmansyah & Muliana (2018) Pretax book income is operating profit plus other income less other expenses before the applicable tax rate under tax regulations (Firmansyah & Muliana, 2018;Guenther et al, 2013).…”
Section: (2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Harjito & Hapsari (2016) and Rajverma et al (2019) concluded that leverage, firm size, and profit before tax are proven to have a negative effect on firm risk. Leverage is a ratio that measures long-term and shortterm debt capacity to finance company assets (Geno et al, 2022). The proxy of leverage in this study is based on Firmansyah & Muliana (2018) Pretax book income is operating profit plus other income less other expenses before the applicable tax rate under tax regulations (Firmansyah & Muliana, 2018;Guenther et al, 2013).…”
Section: (2)mentioning
confidence: 99%
“…At the international level, studies that have examined the effect of variables that are associated with firm risk include corporate governance (Haider & Fang, 2016;Lenard et al, 2014;Mathew et al, 2018), c o r p o r a t e s o c i a l r e s p o n s i b i l i t y (Albuquerque et al, 2019;Nguyen & Nguyen, 2015), firm size (Rajverma et al, 2019), leverage (Rajverma et al, 2019), market-to-book (Rajverma et al, 2019) and profitability (Rajverma et al, 2019), tax aggressiveness (Guenther et al, 2013), tax risk (Guenther et al, 2013;Hutchens & Rego, 2015), and tax avoidance (Guenther et al, 2013;Hutchens et al, 2020). In Indonesia, firm risk testing has been conducted, including gender board (Hatane et al, 2019), independence of the board of directors (Hatane et al, 2019), ownership of the board of directors (Hatane et al, 2019), board size (Hatane et al, 2019), financial leverage (Geno et al, 2022;Sidauruk & Pangestuti, 2015), derivatives (Candradewi & Rahyuda, 2019;Firmansyah et al, 2020a), firm size (Sidauruk & Pangestuti, 2015), profitability (Sidauruk & Pangestuti, 2015), financial performance (Candradewi & Rahyuda, 2019), corporate governance disclosure (Candradewi & Rahyuda, 2019), liquidity (Sidauruk & Pangestuti, 2015), avoidance (Firmansyah & Muliana, 2018) and tax risk (Firmansyah & Muliana, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Firm size is a scale that can be classified as large or small by looking at total assets, log size, stock market value, and others. Measurement of company size used the natural log of total assets (Geno et al, 2022).…”
Section: Controlmentioning
confidence: 99%
“…Meanwhile, several studies also examined similar tests using developing countries' data (Firmansyah, Sihombing, et al, 2020;Januardi & Afrianto, 2017;Kumari et al, 2017). Other financial information which is employed to examine idiosyncratic risk is earnings management (Firmansyah & Suhanda, 2021;Prakosa et al, 2022;Rajgopal & Venkatachalam, 2011;Zhou et al, 2016), leverage (Geno et al, 2022), and earnings volatility (Widyansyah et al, 2021). Furthermore, the previous examinations of idiosyncratic risk were conducted using non-financial company information such as corporate governance (Ghafoor et al, 2019), corporate social responsibility disclosure (Kong et al, 2020;Tzouvanas et al, 2020), board of commissioners (Butar Butar, 2020), and manager competence (Tan & Liu, 2016;Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%